The Politicization of Islamic Society in Post Soviet Russia - Alaverdov, Emilia (Journal of Education Culture and Society, 2020)
Aim. The paper analyses the Islamic revival in Russia in the late 20th century and early 21st. This was reflected in the registration of religious communities, the publication of periodicals on Muslim literature, and, in my opinion, most importantly - the construction of mosques and madrassas. It highlights the roles of mosques and madrassas built in the North Caucasus, which later became the theological centers for the spread of Islam and educated youngsters according to their propaganda. Methods. The study mainly uses an analysis method based on the study of historicism, documents and empirical material. The basis of the source are books, scientific articles, research works conducted by Russian and foreign experts. Results. The post-Soviet wars (1994-1996 and 1999-2000) in Chechnya contributed to the politicisation and realisation of Islam in this region. In 1996-1999 there were 26 Sharia courts, numerous Islamic parties, charitable foundations and organisations in the republic and, most importantly, structures of Wahhabi organisations (Akaev, n.d.). The process of politicisation gradually turned into organisational formations in Russia in the late 1980s and early 1990s. Conclusion. The constructive transformation by reinforcing the modernist potentials of Islam has contributed to the real renewal of Russian Muslim societies, which led to the radicalisation of the whole region. The described events have shown that for the last 20 years, the revival of religious Islam was a revival of political organisations and activities, where religion is connected to politics and criminal activities. A small North Caucasian republic immediately turned up at the center of Russia’s recent history. Key Words: Islam, politics, revival, radicalization, Russia, North Caucasus